If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(-9 + -2x) = -1(12x + 11) (-9 * 11 + -2x * 11) = -1(12x + 11) (-99 + -22x) = -1(12x + 11) Reorder the terms: -99 + -22x = -1(11 + 12x) -99 + -22x = (11 * -1 + 12x * -1) -99 + -22x = (-11 + -12x) Solving -99 + -22x = -11 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -99 + -22x + 12x = -11 + -12x + 12x Combine like terms: -22x + 12x = -10x -99 + -10x = -11 + -12x + 12x Combine like terms: -12x + 12x = 0 -99 + -10x = -11 + 0 -99 + -10x = -11 Add '99' to each side of the equation. -99 + 99 + -10x = -11 + 99 Combine like terms: -99 + 99 = 0 0 + -10x = -11 + 99 -10x = -11 + 99 Combine like terms: -11 + 99 = 88 -10x = 88 Divide each side by '-10'. x = -8.8 Simplifying x = -8.8
| i+30=28 | | 4(-5+x)=48 | | 3x+8=(6-x) | | 2(x-16)-5(x-3)=18 | | 6[x-10]+8=26 | | 7z+17=6z+8 | | 16x+5=-37 | | (x+9)(x-3)=(x+1)(x+1) | | [n/10]=3 | | 8-(3+b)=b+-9 | | -[p-4]+9=8 | | -3r-6r=-9 | | 3(x-4)-4(3-x)=x+3-(x-5) | | 5(x^2-x-12)=0 | | N/-0.5=13 | | 42=-6+4b | | 4y^2-81y=0 | | -7u+3(u+7)=29 | | (f-1)=45 | | -(xy+y^2-4)= | | 18-6x=2x+34 | | 40+12.50= | | 5(x^2-x-30)=0 | | 39=-10x-1 | | 9x+7=20x-7 | | 12.50+40= | | -2+v=4 | | 1.98=(8.99*10^9)*(11.7*10^-6)*(29.9*10^-6)/r^2 | | -2z-7y=7+7 | | 4x-12x+3=5 | | x-2(-2x+5)=2 | | 12x+22=-9x-41 |